Profiling azole resistant haplotypes within Zymoseptoria tritici populations using nanopore sequencing - Gutierrez Vazquez, Yaiza; Adams, Ian P.; McGreig, Sam; Walshaw, John; van den Berg, Femke; Sanderson, Roy; Pufal, Hollie; Conyers, Chris; Langton, David; Broadhead, Ruth; Harrison, Catherine; Boonham, Neil (Frontiers in Agronomy, 2022)
Zymoseptoria tritici is the causal agent of Septoria tritici blotch, the most important disease affecting wheat crops and responsible for up to 50% loss in yield. Azoles and SDHIs are the main groups of fungicides used to control the disease. The efficacy of these fungicides has decreased in recent years due to resistance development. Resistance can be a result of mutations in the target genes, mutations in upstream regulatory elements that result in over-expression of target proteins and the overexpression of transporters that remove toxic compounds from cells. In the current study nanopore sequencing was used to analyse isolates, mock communities and field samples to determine the pathogen population composition related to azole resistance. Despite the presence of sequencing errors, the method was able to effectively differentiate the sequences of different haplotypes present in both mock and field populations for haplotypes that were relatively common in the overall population. However, rare haplotypes, present at a frequency lower than 5% of the total population, could not be accurately distinguished from haplotypes generated through background sequencing errors. The method is however fast and inexpensive and could be useful for analysing populations at the start of the season or between sprays to better understand the mutations present in the most abundant haplotypes of the populations to facilitate selection of the most appropriate fungicide to control them, yet limit further selection for azole resistance.